2016
DOI: 10.1108/lm-05-2016-0038
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for sustainable services in academic libraries

Abstract: Purpose The purpose of this paper is to explore distinctive yet simple strategies for sustainability in academic libraries focussing on structured communication templates for stakeholders, pre-planned daily programming, and regularized, self-sustaining staff development. Design/methodology/approach Case study of unique strategies implemented at Nanyang Technological University Libraries. Findings Each of the three strategies has been successfully launched though they are at various stages of maturity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Publications on sustainable library development are characterized by the optimization of internal library practices and workflows. We see this in publications on sustainable organizations and leadership (Michael, 2010) or sustainable strategies and services (Cottrill et al, 2015;Cmor, 2016). University librarian Wilson (2012, p. 78) stresses that "sustainability is the capacity to endure," which entails making the most of the library's resources, understood both as monetary resources but also as staff competencies, time and material equipment.…”
Section: An Environmental Understandingmentioning
confidence: 99%
See 3 more Smart Citations
“…Publications on sustainable library development are characterized by the optimization of internal library practices and workflows. We see this in publications on sustainable organizations and leadership (Michael, 2010) or sustainable strategies and services (Cottrill et al, 2015;Cmor, 2016). University librarian Wilson (2012, p. 78) stresses that "sustainability is the capacity to endure," which entails making the most of the library's resources, understood both as monetary resources but also as staff competencies, time and material equipment.…”
Section: An Environmental Understandingmentioning
confidence: 99%
“…This goes for both material resources, such as electricity, paper and plastic bags (Beutelspacher and Meschede, 2020), and immaterial resources, such as practices and workflows (cf. Michael, 2010;Cmor, 2016;Cottrill et al, 2015). The optimization rationale also concerns optimizing digital services (see Michnik, 2015;Koukopoulos et al, 2019) and finding new creative solutions for doing more with less (cf.…”
Section: Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) what was offered to our users; and (3) impact of the service/event/resource/tool." 18 Sarah McNicol discusses ways that strategic plan priorities and results are communicated to campus actively, such as in formal committee settings, or passively, such as through annual reports. 19 Kaitlin Springmier, Elizabeth Edwards, and Michelle B. Bass provide a benchmark on how academic libraries communicate their assessment projects publicly and found that libraries are using not just numbers, but also narratives and stories to provide context for the quantitative data collected.…”
Section: Communicating Valuementioning
confidence: 99%